2021
DOI: 10.1101/2021.09.22.461338
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of genetic risk for Alzheimer’s disease on the structural brain networks of young adults

Abstract: To facilitate pre-symptomatic diagnosis of late-onset Alzheimers disease, non-invasive imaging biomarkers could be combined with genetic risk information. In this work, we investigated the structural brain networks of young adults in relation to polygenic risk for Alzheimers disease, using magnetic resonance imaging (MRI) and genotype data for 564 19-year-old participants from the Avon Longitudinal Study of Parents and Children. Diffusion MRI was acquired on a 3T scanner, and the data were used to perform whol… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 124 publications
(125 reference statements)
0
1
0
Order By: Relevance
“…AD-PRS was also found to be associated with reduced FA and increased mean diffusivity across the whole brain white matter tracts, notably in the inferior occipitofrontal fascicle, superior longitudinal fascicle, cingulum and corpus callosum in the AD patients (Harrison et al, 2020a ). Recently, Mirza-Davies et al ( 2021 ) found the visual subnetwork constructed based on dMRI was also correlated with AD-PRS.…”
Section: Associations Of Ad-prs With Neuroimaging Biomarkersmentioning
confidence: 99%
“…AD-PRS was also found to be associated with reduced FA and increased mean diffusivity across the whole brain white matter tracts, notably in the inferior occipitofrontal fascicle, superior longitudinal fascicle, cingulum and corpus callosum in the AD patients (Harrison et al, 2020a ). Recently, Mirza-Davies et al ( 2021 ) found the visual subnetwork constructed based on dMRI was also correlated with AD-PRS.…”
Section: Associations Of Ad-prs With Neuroimaging Biomarkersmentioning
confidence: 99%